Validation of turbulence models through SCADA data - Nils Gerke and Inga Reinwardt and Peter Dalhoff and Matthias Dehn and Wolfgang Moser (Journal of physics / Conference Series, 2018)
This analysis compares engineering turbulence models to SCADA measurements from operating wind farms. The investigated models are S. Frandsen, G.C. Larsen and D.C. Quarton, which all overestimate the wake added turbulence intensity. The model closest to the SCADA measurements is the model of G.C. Larsen, which confirms the findings of T. Sørensen et.al in [1].